Efektivitas Program Pelatihan Kewirausahaan DPKUKMP bagi Pelaku UMKM di Kota Palangkaraya - Melnayati Melnayati; Sofia Latanzha; Murraya Putri Palupi; Bhayu Rhama (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to assess the effectiveness of the entrepreneurship training program for Micro, Small, and Medium Enterprises (MSMEs) held by the Palangka Raya City Department of Trade, Cooperatives, Small and Medium Enterprises, and Industry (DPKUKMP) on August 20-21, 2025. This study uses a qualitative approach, data collection is obtained through interviews and documentation to evaluate the program's impact on knowledge, managerial skills, digital adaptation, and business performance of MSMEs participants. This research is measured based on the simamora indicators, namely reactions, learning, behavior, and results. From the study, it was found that there was a positive response from participants, meaning that this program is effective, indicating success in fostering entrepreneurship. For DPKUKMP Palangka Raya City, this program makes a significant contribution to the development of the entrepreneurial ecosystem and strengthens the competitiveness of MSMEs in the digital era. The implications show that such a program can be a targeted policy recommendation for the development of sustainable MSMEs in Palangkaraya, encouraging digital adaptation and financial management to improve business performance and local economic growth.